2023
DOI: 10.3390/biomedicines11061606
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Chronic Kidney Disease and Alzheimer’s Disease: A Longitudinal Follow-Up Study Using the Korean National Health Screening Cohort

Abstract: Chronic kidney disease (CKD) and Alzheimer’s disease (AD) are common chronic diseases in the elderly population. Although a relationship between CKD and the occurrence of AD has been proposed, previous research results have been disputed, and further investigation is necessary to confirm this relationship. In this longitudinal follow-up study, we examined data from the Korean National Health Insurance Service-Health Screening Cohort, consisting of 15,756 individuals with CKD and 63,024 matched controls aged ≥4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Several cohort studies have shown that patients with CKD have a higher risk of subsequently developing Parkinson’s disease than control groups [ 14 , 15 , 16 ]. Conversely, a recent study advocated that no significant correlation was observed between these two conditions [ 36 ]. However, this study also described an increased likelihood of developing Parkinson’s in patients with specific lifestyles and comorbidities, such as rural residents, normal weight, and hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies have shown that patients with CKD have a higher risk of subsequently developing Parkinson’s disease than control groups [ 14 , 15 , 16 ]. Conversely, a recent study advocated that no significant correlation was observed between these two conditions [ 36 ]. However, this study also described an increased likelihood of developing Parkinson’s in patients with specific lifestyles and comorbidities, such as rural residents, normal weight, and hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…CKD was defined as either receiving a diagnosis of CKD (ICD-10 code N18) or being diagnosed with unspecified renal failure on at least two separate occasions, with the inclusion of individuals undergoing routine dialysis treatment, including hemodialysis and/or peritoneal dialysis, if their records contained relevant therapeutic codes (O7010, O7020, and O7070) [4].…”
Section: Exposure (Ckd) and Outcome (Migraine)mentioning
confidence: 99%
“…The CCI was employed as a continuous variable, encompassing a score ranging from 0, indicating the absence of comorbidities, to 29, representing the existence of diverse comorbidities [25,26]. The selection of covariates for adjustment was based on a review of the literature indicating potential confounders in the association between CKD and migraine incidence [2][3][4][5][17][18][19], ensuring a robust statistical analysis.…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation